Resveratrol entrapped niosomes as yoghurt additive. (1st March 2015) - Pando, D.; Beltrán, M.; Gerone, I.; Matos, M.; Pazos, C.
Graphical abstract: Highlights: Nanodesign of food-grade niosomes containing resveratrol (RSV) was performed. Dodecanol was used as stabiliser of niosome membrane. Niosomes were produced by a modified thin film hydration method. Factorial design of experiments and statistical analysis of variance were applied. A functional yoghurt was successfully prepared by adding RSV entrapped niosomes. Abstract: Nanodesign of niosomes containing resveratrol (RSV) was carried out using food-grade surfactants with dodecanol to stabilise the membrane. Niosomes were prepared using a modified thin film hydration method. A factorial design analysis was carried out to reduce the number of experiments. The response factors were: mean size, polydispersity index (PDI) and entrapment efficiency (EE). Agitation speed and surfactant to dodecanol weight ratio were selected as key parameters for niosomes preparation. Parameter contribution was determined using a statistical analysis of variance (ANOVA). Niosomes formulated with Span 60 or Maisine 35-1 as surfactants, and dodecanol as stabiliser, were able to incorporate RSV. These niosomes exhibited a small mean size, narrow size distribution, high RSV entrapment efficiency and good stability. RSV addition did not involve changes in the textural properties of regular yoghurt demonstrating that RSV entrapped niosomes are suitable additives in these dairy products.